Human, Technologies and Quality of Education, 2020 2020
DOI: 10.22364/htqe.2020.05
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a Child With a Hearing Impairment in a Mainstream School, Single Case Study

Abstract: Inclusive education means that all pupils, regardless of their ability, gender and race, can study with their peers in the school closest to their place of residence. When enrolling students with special needs in a school, the quality of the student’s academic and social inclusion is equally important. The study aims to analyze the single case of inclusion of a boy with a hearing impairment in a mainstream school X to answer the research questions: how do teachers deal with a pupil with hearing impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Teachers have not talked about the use of realia. However, similar to the results of many studies conducted from the past to the present, (Miller, 1995;Nīmante & Ekša, 2020;Pérez-Jorge et al, 2021;Slobodzian, 2009), the participants stated that the classrooms were crowded. All participants emphasized that this situation negatively affects the participation and interaction of students with hearing loss in the lessons.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 81%
See 4 more Smart Citations
“…Teachers have not talked about the use of realia. However, similar to the results of many studies conducted from the past to the present, (Miller, 1995;Nīmante & Ekša, 2020;Pérez-Jorge et al, 2021;Slobodzian, 2009), the participants stated that the classrooms were crowded. All participants emphasized that this situation negatively affects the participation and interaction of students with hearing loss in the lessons.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 81%
“…In the studies on teachers' opinions from the past and the present, it has been found that there are problems related to the physical conditions of the inclusion environment, the characteristics of the hearing impaired student(s), and the quality of the resource room (Aslan, 2019;Atmaca & Uzuner, 2020;Cambra, 2002;Coladarci & Breton, 1997;Gurgur et al, 2016;Slobodzian, 2009;Watson et al, 1999;Yazicioglu, 2020). In many studies, the focus of these problems and possible solutions have been shown to be related to teachers' perspectives on inclusion (Aslan, 2019;Eriks-Brophy & Whittingham, 2013;Nīmante & Ekša, 2020). In this study, the participants' opinions and experiences about the inclusion practices and the contributions/problems of the educational support service were examined in depth through focus group interviews.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 98%
See 3 more Smart Citations